PROXIMATE AND MINERAL COMPOSITIONS OF FRESH ATLANTIC MACKEREL (Scomber scombrus) SOLD IN MAJOR MARKETS WITHIN GOMBE METROPOLIS, GOMBE STATE, NIGERIA - Abdullahi, B.A.; Ahmad, M.K.; Baba, H.A.; Bello, L. H.; Yusuf, A.; Adeoye, D.B.; Ngdede, S.O.; Shaibu, C.N. (Kashere Journal of Animal Science, 2025)
The study determined the proximate composition and Mineral Compositions of Atlantic mackerel (Scomber scombrus) sold in various markets within Gombe Local Government of Gombe State. Atlantic mackerelis one of the most commercialized marine fish species consumed in Nigeria due to its high nutritional values. Fresh samples of Atlantic mackerel sold in Gombe local markets were bought, chilled in an ice in a plastic container and transported to the D epartment of Animal Science, Federal University of Kashere for Mineral and Proximate Analysis. The samples were purchased in triplicates from the four major Gombe markets and were tagged as; New Market (A), Old Market (B), Tashan Dukku (C) Pantami Market (D). Proximate analysis was conducted using the Association of Official Analytical Chemists (AOAC 2005) method to determine the Protein, Fiber, Moisture, Ether Extract and ash. Mineral contents of the samples were determined by atomic absorption spectrometry, flame photometry and spectrophotometry method.Mineral elements detected includes; Potassium (K), Iron, Copper, Phosphorous and Zinc. Results showed that highest mean value of the moisture, ash, ether extract, crude fiber, and crude protein contents in percent (%) as: 75.92, 1.22, 7.55, 1.10 and 19.65 respectively. The mineral composition was found to be higher in D with 148.52 (Phosphorous), A 14.67 (Zinc), C 11.93 in Copper, 3.02 (D) in Iron and 192.03 in Potassium with treatment D. In conclusion, the study revealed that there is a significant differences in nutritional content among fish sourced from the various markets. Both fish sold in the markets are rich in essential nutrients and minerals, making them a valuable food source. The findings also highlight the importance of marine species in human nutrition and health. Results from this study can also inform policy makers on food security and nutrition to regulate the available fish species sold in the major markets for public health concern.